Integrating Project-Based Learning with iNaturalist to Enhance Biodiversity Literacy - Apriliani, Anti; Badriah, Liah; Nuryadin, Egi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study investigated the effect of an iNaturalist-assisted Project-Based Learning (PjBL) model on students’ biodiversity literacy in the context of biodiversity education. A quasi-experimental method with a nonequivalent control group design was employed. The participants were Grade 10 students at SMA Negeri 8 Tasikmalaya during the 2025/2026 academic year, selected using purposive sampling. The experimental group received iNaturalist-assisted PjBL, the positive control group received PjBL without iNaturalist, and the negative control group received Discovery Learning. Biodiversity literacy was assessed using a validated and reliable 36-item multiple-choice test. The data were analyzed using analysis of covariance (ANCOVA) at a 5% significance level, followed by the Least Significant Difference (LSD) post hoc test. The ANCOVA results demonstrated that the iNaturalist-assisted PjBL model had a significant effect on students’ biodiversity literacy (F = 39.992, p < 0.001). The LSD test further confirmed that the experimental group achieved the highest mean score (32.66), significantly exceeding the PjBL group without iNaturalist assistance (23.85) and the Discovery Learning group (19.73). These findings indicate that integrating citizen science technology into the PjBL framework significantly enhances students’ biodiversity literacy. The statistically significant differences among the three groups provide empirical evidence that combining project-based instruction with digital species-identification technology is more effective in facilitating students’ mastery of biological concepts than the other instructional approaches examined.